The Appearance of Accountability: Communication Technologies and Power Asymmetries in Humanitarian Aid and Disaster Recovery - and Madianou, Mirca; Ong, Jonathan Corpus; Longboan, Liezel; Cornelio, Jayeel S. (Journal of Communication, 2016)
New communication technologies are celebrated for their potential to improve the accountability of humanitarian agencies. The response to Typhoon Haiyan in 2013 represents the most systematic implementation of “accountability to affected people” initiatives. Drawing on a year-long ethnography of the Haiyan recovery and 139 interviews with humanitarian workers and affected people, the article reveals a narrow interpretation of accountability as feedback that is increasingly captured through mobile phones. We observe that the digitized collection of feedback is not fed back to disaster-affected communities, but is directed to donors as evidence of “impact.” Rather than improving accountability to affected people, digitized feedback mechanisms sustained humanitarianism's power asymmetries.
Keywords: Accountability; Audit; Communication for Development; Disasters; Ethnography; ICT4D; Mobile phones; Participatory Communication; SMS; Texting; humanitarianism